(untitled) (Research, Society and Development, 2022)
Kombucha is a non-alcoholic fermented tea-based beverage produced by a symbiotic culture of bacteria and yeast. This growing popularity in the United States and developed countries has been part of the functional food’s movement in the use of plant infusions as a promising alternative to the benefits of the microbiome in the treatment of obesity and diabetes. However, recent studies show controversial information about the effects of Kombucha on health, often driven by different theories leading to the empirical use of the drink without standardization of quantity and forms, and preparation, which can cause harm to human health. Given that, we carried out this systematic review to evaluate the effect of Kombucha on health through pre-clinical studies with scientific evidence available in the literature, to enable future studies in humans.